Pengaruh Lingkungan Kerja Fisik Dan Komunikasi Terhadap Kinerja Pegawai Di UPTD Puskesmas Pesantren I Kediri - Iis Rahayu; Erwin Syahputra; Anita Sumelvia Dewi (Akuntansi, 2022)
This study aim to explain the significant influence between physical work environment and communication on employee performance at UPTD Puskesmas Pesantren I Kediri. The sampel in this study was 36 respondents with a sampling method using purposive sampling technique in which the determination of the number of samples with ertain considerations, namely the criteria of civil servants. The data analysis technique used in this research is instrument validity test, instrument reliabiity test, multiple linear regression test, classical assumption test and partial hypothesis testing which is tested by t test while the simultaneous hypothesis is tested by F test. The result of the study show that the physical work environment partially has a significant influence on the performance of employees at the UPTD Puskesmas Pesantren I Kediri. Communication partially has a significant effect on the performance of employees at the UPTD Puskesmas Pesantren I Kediri. The physical work environment and communication simultaneously have a significant influence on employee performance at the UPTD Puskesmas Pesantren I Kediri. In addition, the coefficient of determination (R2) is 0.397 or 39.7%. This indicates that the performance of the employees of UPTD Puskesmas Pesantren I Kediri is influenced by the physical work environment and communication variables by 39.7%. While the remaining 60.3% came from other variables obtained from previous studies suh as motivation and discipline which were not included in this study.